Epidemiology and Immune Response of Cryptosporidium parvum Infection in Children in Tikrit City - Alwan, Azal Hassan; Athab, Elham Khalef; Kurdy, Rehab Salman (American Journal of Biology and Natural Sciences, 2026)
This study aimed to identify the epidemiological factors associated with the spread of the Cryptosporidium parvum. Samples were collected from patients visiting Tikrit Teaching Hospital in Salah al-Din Governorate. Sample collection continued from September 2025 until December 2026. 150 stool samples were collected from patients whose ages ranged from (6 months to 10 years). Cryptosporidium parvum was detected using modified Ziehl-Neelsen staining in 38% of the samples upon microscopic examination. The infection rate was higher in males (42.1%) compared to females (27.3%). The highest prevalence was observed in the 3- 5year age group (42.1%), while the lowest was in the 6-10 year age group (7.3%). The current immunological study recorded a highly significant increase in the level of Il-2, IL-10, and CCL20 in the affected children, with the average concentration of Il-12 (27.9 ± 2.6 Pg/ml), IL-10 (16.98 ± 1.9 Pg/ml), and CCL20 (231.6 ± 11.1 ng/mL) compared with the control group at p- value ≤ 0.05. Conclusion: The current study concluded a clear prevalence of C. parvum parasite in children, and also demonstrated a clear variation in the distribution of infection according to sex and age. The current study, through the evaluation of certain inflammatory immunological parameters in blood serum samples, concluded that the parasite stimulates an immune response resulting from its infection of intestinal cells in the small intestine, characterized by a highly significant increase in IL-10, IL-12, and CCL20.